Maqasid al-Shari‘ah and Ecotheology: A Philosophical Analysis of the Normative Foundations of Islamic Law in Ecological Issues - Arzam, Arzam; Kusnadi, Kusnadi (Jurnal Mediasas: Media Ilmu Syari'ah dan Ahwal Al-Syakhsiyyah, 2025)
This study philosophically analyzes the normative basis of the relationship between maqasid al-shari'ah and ecotheology as the foundation for forming of Islamic law in response to contemporary ecological issues. Using a qualitative-normative approach combined with hermeneutic-philosophical analysis, the study explores the dimension of maqasid al-syari‘ah particularly the conception of hifz al-bi’ah as a vital additional objective in framing responsive and sustainable Islamic environmental law. The study of Islamic ecotheology is supported by the core principles of tawhid, khalifah-amanah, mizan, and the prohibition of fasad, which shape the ethics and norms of environmental protection. Findings reveal that integrating maqasid al-syari‘ah with ecotheology has the potential to strengthen the normative framework of Islamic law through contemporary ijtihad, environmental fatwas, and the development of community-based legal instruments but still faces challenges such as anthropocentrism, implementation gaps, and the need to harmonize with sustainable development standards. The study concludes there is a necessity to reinforce the paradigm of ecological justice and facilitate intertradition collaboration to realize more effective Islamic legal responses addressing the global ecological crisis. [Penelitian ini menganalisis secara filosofis dasar normatif hubungan antara maqasid al-syari‘ah dan ekoteologi sebagai fondasi pembentukan hukum Islam dalam merespons isu-isu ekologis kontemporer. Dengan pendekatan kualitatif-normatif dan analisis hermeneutis-filosofis, penelitian mengupas dimensi maqasid al-syari‘ah khususnya pemaknaan hifz al-bi’ah sebagai maqasid tambahan yang vital dalam membingkai hukum lingkungan Islam yang responsif dan berkelanjutan. Kajian ekoteologi Islam didukung oleh prinsip utama tawhid, khalifah-amanah, mizan, dan larangan fasad, yang membentuk etika dan norma perlindungan lingkungan. Hasil temuan menunjukkan bahwa integrasi maqasid al-syari‘ah dengan ekoteologi berpotensi memperkuat kerangka normatif hukum Islam melalui ijtihad kontemporer, fatwa lingkungan, dan pengembangan instrumen hukum berbasis komunitas, namun masih menghadapi tantangan antroposentrisme, gap implementasi, serta perlunya harmonisasi dengan standar pembangunan berkelanjutan. Penelitian ini menyimpulkan perlunya penguatan paradigma keadilan ekologis dan kolaborasi lintas tradisi demi mewujudkan hukum Islam yang lebih efektif dalam menjawab krisis ekologis global]